CAMPURAN TERIGU DAN SAGU SEBAGAI EKSTENDER PEREKAT KAYU LAPIS - Suwardi Sumadiwangsa (Pusat Penelitian dan Pengembangan Hasil Hutan, 1986)
In 1983 Indonesian plywood industries consumed about 45 000 tons of wheat flour as an extender of ureaformaldehyde adhesive. This material is imported from foreign country, although Indonesia, as an agricultural country, is rich with carbohydrate resources such as palm trees.The result of a laboratory study on the effect of four wheat and sago flour mixtures and four levels of extender content on plywood property is presented in this paper.The mixtures of wheat and sago flour were 100/0, 80/20, 60/40, and 40/60. Each of them was mixed with the UF glue at four different composition, namely I 5, 20, 25, and 30 percent of each total glue weight.The experiment was based on the 4 x 4 factorial design with. 4 replications.The result shows that the wheat and sago flour mixture does not significantly affect the glue shear as well as the wood failure. The extender content on the other hand, affects significantly the above properties, in which higher extender content has resulted in lower plywood quality. The study reveals also that all of the plywood samples tested conform with the Indonesian Standard (Sil) for plywood type II.